Keragaan Morfologi dan Potensi Hasil Galur-Galur Padi Japonica dengan Kandungan Zn Tinggi di Sawah Irigasi Dataran Rendah - Vania Qinthari; Elia Azizah; Wage Ratna Rohaeni (JURNAL PERTANIAN, 2026)
Rice is the staple food for 90% of the Indonesian population, yet its grain Zn content is generally low, contributing to potential micronutrient deficiencies. Japonica rice, known for its sticky texture, has the potential to contain higher Zn levels, making it a promising candidate to support the national stunting prevention program. This study aimed to evaluate the morphological variation of high-Zn Japonica rice lines cultivated in irrigated lowland fields and to identify lines that outperform existing varieties. A single- factor Randomized Complete Block Design (RCBD) was used, consisting of 56 lines and 4 control varieties, with two replications, resulting in 120 experimental units. Observed variables included plant height, number of productive tillers, flowering time, maturity time, and panicle length. Data were analyzed using the F-test, followed by the Least Significant Increase (LSI) test at a 5% significance level when significant effects were detected. Line IR 134409-B-41-1-1 had the tallest plants, averaging 103.75 cm. The highest number of productive tillers was found in IR 134422-B-26-1 (32.75 tillers). The earliest flowering was observed in IR 134422-B-37-1 (58 days after sowing), and the earliest maturity in IR19K1059 (92 days). The longest panicle length was recorded in B14806D-MR-6-4-KN-5 (26.17 cm). Line IR 134421-B-31-1 showed high potential with a dry milled grain yield of 7.53 tons/ha and a Zn content of 31.15 ppm, closely matching the control Inpari IR Nutri Zinc